Differentiating Between Moffitt's Developmental Taxonomy and Silverthorn and Frick's Delayed-Onset Models of Female Offending. (April 2017) - El Sayed, Sarah A.; Piquero, Alex R.; TenEyck, Michael
It is a criminological fact that females commit fewer delinquent acts than their male counterparts. This "gender gap" has long been recognized but specific questions concerning similarities or differences in the development, persistence, and desistence of antisocial behavior among females and males remain underinvestigated. Two prominent theoretical models, Moffitt's developmental taxonomy and Silverthorn and Frick's delayed-onset pathway, make distinct predictions about the composition of female offenders and the nature of their offending. The current study tests these explanations using longitudinal data from the Pathways to Desistance Study, a large sample of serious juvenile offenders followed for 7 years into early adulthood. Results from a series of negative binominal regressions reveal stronger support for Moffitt rather than Silverthorn and Frick in that findings showed two groups of female offenders. Directions for future research are highlighted.